Clinicopathologic Characteristics and Survival in BRCA1- and BRCA2-Related Adnexal Cancer: Are They Different?. Issue 4 (1st May 2012) - Reitsma, Welmoed; de Bock, Geertruida H.; Oosterwijk, Jan C.; ten Hoor, Klaske A.; Hollema, Harry; Mourits, Marian J. E.
Abstract : Objective: Our aim was to examine the clinicopathologic characteristics and survival of ovarian, tubal, and peritoneal (further denoted "adnexal") cancer in BRCA1 compared with BRCA2 carriers. Methods: A consecutive series of adnexal cancers in BRCA1/2 mutation carriers diagnosed in 1980 to 2010 at the University Medical Center Groningen was analyzed. Results: We evaluated 55 BRCA1- and 16 BRCA2- related adnexal cancers, consisting of 51 ovarian, 13 tubal, and 7 peritoneal cancers. Peritoneal cancer was restricted to BRCA1 carriers. Ovarian and tubal cancer was equally present in both carrier groups. Median age at diagnosis was younger in BRCA1 compared with BRCA2 carriers (50 vs 54 years; P = 0.03). No other clinicopathologic differences were found. Regarding survival, a nonsignificant trend was noted for BRCA2 carriers to have fewer relapses, a longer time to first relapse, and a longer disease-free and overall survival. Conclusions: Except for age at diagnosis and prevalence of peritoneal cancer, no significant clinicopathologic differences were found between BRCA1 - versus BRCA2 -associated adnexal cancer. On survival, it might be suggested that BRCA2 carriers have a more favorable outcome than BRCA1 carriers, marked by fewer relapses, a longer time to first relapse, and a longer disease-free and overall survival.